RELEVANSI ERA REVOLUSI INDUSTRI 4.0 DAN ERA MASYARAKAT 5.0 DENGAN TIGA PILAR PENDIDIKAN ISLAM DI INDONESIA - Andi Syahputra (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
In Indonesia, the industrial revolution 4.0 era and the Society 5.0 era have changed the human mindset and life in various fields, including Islamic education. Implementing Islamic education can refer to the three pillars of Islamic education. Therefore, this study aims to determine the changes in the industrial revolution 4.0 era and the Society 5.0 era and their relevance to the three pillars of Islamic education. The research method uses a qualitative literature review or library research methodology. The data collection technique uses library data as the main source relevant to this research, such as several books, journals, theses, dissertations, research reports, encyclopedias, documents, magazines, etc. Then, the data is read, recorded, processed, and analyzed more intensely to get the facts. The results of this study indicate that the drastic changes in the implementation of Islamic education that occurred in the industrial revolution 4.0 era and the Society 5.0 era in Indonesia must remain relevant to the three pillars of Islamic education, namely tauhid education, akhlak education, and ibadah education.